2022
DOI: 10.20517/2347-9264.2021.34
|View full text |Cite
|
Sign up to set email alerts
|

Intra-abdominal donors for vascularized lymph node transfer: an update and review

Abstract: Lymphedema continues to be a very challenging clinical problem. While compression and physical therapy remain the foundation of treatment, recent advances in microsurgery and super-microsurgery have allowed for the development of promising surgical options. One of these options is vascularized lymph node transfer (VLNT), which has gained significant popularity over recent years. However, there is no consensus on the ideal donor lymph node basin for VLNT. In addition, the most commonly reported donor sites, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…Omentum is the most often used intra-abdominal flap. 30 It is potentially an ideal donor candidate because of its high degree of vascularization, large in size, vast lymphatic channels, and lymphatic lakes. 30,31 Our study revealed that VLNT interventions resulted in substantial CRR of the upper limb.…”
Section: Limb Circumference Reduction Rate and Postoperative Infectio...mentioning
confidence: 99%
“…Omentum is the most often used intra-abdominal flap. 30 It is potentially an ideal donor candidate because of its high degree of vascularization, large in size, vast lymphatic channels, and lymphatic lakes. 30,31 Our study revealed that VLNT interventions resulted in substantial CRR of the upper limb.…”
Section: Limb Circumference Reduction Rate and Postoperative Infectio...mentioning
confidence: 99%
“…In recent years, additional donor sites for lymphatic tissue have been found. There are several benefits to obtaining lymph nodes and tissue from the abdominal cavity, as it can mitigate the risk for donor-site lymphedema-a major concern when it comes to VLNTs from extra-abdominal sites [48] . Intra-abdominal sites also allow for the ability to harvest up to 3 vascularized flaps from 1 donor site [48] .…”
Section: Intra-abdominal Vs Extra-abdominalmentioning
confidence: 99%
“…There are several benefits to obtaining lymph nodes and tissue from the abdominal cavity, as it can mitigate the risk for donor-site lymphedema-a major concern when it comes to VLNTs from extra-abdominal sites [48] . Intra-abdominal sites also allow for the ability to harvest up to 3 vascularized flaps from 1 donor site [48] . With the possibility of laparoscopic harvest, the risk of donor-site morbidity may be reduced and minimal donor-site scars can be well-hidden [48,49] .…”
Section: Intra-abdominal Vs Extra-abdominalmentioning
confidence: 99%
See 2 more Smart Citations